Pan-cancer analyses confirmed the cuproptosis-related gene FDX1 as an immunotherapy predictor and prognostic biomarker - Zhang, Chi; Zeng, Yuanxiao; Guo, Xiuchen; Shen, Hangjing; Zhang, Jianhao; Wang, Kaikai; Ji, Mengmeng; Huang, Shengwei (Frontiers in Genetics, 2022)
Background: The latest research identified cuproptosis as an entirely new mechanism of cell death. However, as a key regulator in copper-induced cell death, the prognostic and immunotherapeutic value of FDX1 in pan-cancer remains unclear. Methods: Data from the UCSC Xena, GEPIA, and CPTAC were analyzed to conduct an inquiry into the overall differential expression of FDX1 across multiple cancer types. The expression of FDX1 in GBM, LUAD and HCC cell lines as well as their control cell lines was verified by RT-QPCR. The survival prognosis, clinical features, and genetic changes of FDX1 were also evaluated. Finally, the relationship between FDX1 and immunotherapy response was further explored through Gene Set Enrichment Analysis enrichment analysis, tumor microenvironment, immune cell infiltration, immune gene co-expression and drug sensitivity analysis. Results: The transcription and protein expression of FDX1 were significantly reduced in most cancer types and had prognostic value for the survival of certain cancer patients such as ACC, KIRC, HNSC, THCA and LGG. In some cancer types, FDX1 expression was also markedly correlated with the clinical characteristics, TMB, MSI, and antitumor drug susceptibility or resistance of different tumors. Gene set enrichment analysis showed that FDX1 was significantly associated with immune-related pathways. Moreover, the expression level of FDX1 was confirmed to be strongly correlated with immune cell infiltration, immune checkpoint genes, and immune regulatory genes to a certain extent. Conclusion: This study comprehensively explored the potential value of FDX1 as a prognostic and immunotherapeutic marker for pan-cancer, providing new direction and evidence for cancer therapy.